Social exclusion and access to social protection schemes. Issue 2 (3rd April 2017) - Kidd, Stephen
ABSTRACT: This article examines the barriers that people in developing countries face when attempting to access social protection schemes, and the extent to which this is explained by social exclusion. It shows how eligible people are excluded from social protection schemes for multiple and complex reasons, including policy decisions on coverage and budgets, challenges caused by scheme design and implementation, and differing capabilities of people to access schemes and overcome barriers to inclusion. Furthermore, the paper also describes how exclusion not only happens during the identification and registration of beneficiaries but also at other points in the operational cycle of social protection programmes, such as during the payment of transfers and enforcement of conditions. The paper also shows how barriers to exclusion have been addressed, drawing on experience from across the world.